A study on “Repetitive Motifs” in selected billboard top charters from 2000-2013 / Gloria Chin Jin Yu - Gloria , Chin Jin Yu (2016)

(untitled)
Literature review informs the usage of repetitive motif in music composition and one of its functions in structuring musical hook in music composition reveals the factors contributing to the popularity in popular music. Past studies examined the effects of repetition in retrieving listeners’ preferences and most studies had proven positive results. However, the term “repetition” was perceived as repeating the complete music over and over again on a macro level. Thus, there is still a lack of research looking into the smaller unit of repetition within a larger frame; and in this study, repetitive motif is examined. Chart-topping hits which were taken from Billboard Year End Hot 100 from 2000-2013 were selected and analysed. Methodology includes qualitative and quantitative approaches: listening and score analysis, and measurement of the repetitive motif duration and frequency of appearance. The outcome reveals how a repetitive motif is employed in a popular song context based on various musical parameters, its density in terms of occurrence, and its construction and repetition within a larger frame of structural repetition.